2020
DOI: 10.1016/j.jcot.2020.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome of High Tibial Osteotomy in Patients with Medial Compartment Osteoarthritis Using Dynamic Axial Fixator -a prospective study

Abstract: Introduction: Medial Compartment Osteoarthritis of the knee is becoming a widespread problem. The surgical options include high tibial osteotomy, unicompartmental knee replacement, and total knee replacement. Replacement surgeries are not advised in the younger age group, so in these patients, high tibial osteotomy is the only option. In this study, we have assessed the functional and radiological outcomes of high tibial osteotomy done by hemicallostasis method. Method: We report the outcome of 30 patients (30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…This study found greater postoperative HKA and MAD values to exhibit some association with superior knee function following HTO; a finding that is well supported within the current literature[ 55 , 56 ]. These results suggest that a more valgus knee positioning, and further lateral position of the lower limb mechanical axis, may be associated with improved knee function one year following HTO.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study found greater postoperative HKA and MAD values to exhibit some association with superior knee function following HTO; a finding that is well supported within the current literature[ 55 , 56 ]. These results suggest that a more valgus knee positioning, and further lateral position of the lower limb mechanical axis, may be associated with improved knee function one year following HTO.…”
Section: Discussionsupporting
confidence: 88%
“…The mean postoperative MAD of the HTO group was 59.9%, which approximated Fujisawa’s point: the target alignment point during preoperative planning, which is reported in the literature to be located at 62.5% of the tibial width (Table 6 )[ 58 ]. Several studies, including a meta-analysis and systematic review, report under correction as the most common cause of unsatisfactory results following HTO[ 5 , 55 , 59 ]. Conversely, increased HKA/MAD values are associated with an increased risk of lateral compartment degeneration; which may ultimately necessitate the conversion of HTO to total knee arthroplasty[ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“… ∥ References 1-3, 4-9, 12-14, 16-21, 23-36, 39-44, 46, 50-54, 56, 57, 59-63, 65-67, 69-79, 81, 83-85, 92, 93. …”
mentioning
confidence: 99%